Analysis of the various Security Attacks and Countermeasures in Cognitive Radio Network - Singh, Jagsir; Singh, Jaswinder (International Journal of Computer Sciences and Engineering, 2025)
The cognitive radio technology is one of the best candidates to handle the problem of the scarcity of the radio spectrum. The basic principle of cognitive radio is that it allows to secondary users to use the free (idle) primary channels. The cognitive radio networks do not only face the traditional security attacks, but also new security attacks due to the new characteristics of the cognitive radio technology. A number of the major news attacks in the Cognitive Radio Networks (CRNs) are the primary user emulation, spectrum sensing data forgery, and jamming attacks. In wireless networks, security is a challenging aspect. In the CRN, it is much more difficult because Cognitive Radios (CR) performs the various functions such as sensing the radio spectrum, managing the spectrum, spectrum mobility and sharing the spectrum. To perform all these functions efficiently without any attack, security mechanisms are required to implement. In this paper, major security attacks in the cognitive radio networks are discussed. Also, the various countermeasures to these security attacks in CRN are described.